KETERAMPILAN PROSES SAINS SISWA SMA PADA MATERI LAJU REAKSI MENGGUNAKAN MODEL PEMBELAJARAN INKUIRI TERBIMBING - Pisdon, Perezcky Paulus; Enawaty, Eny; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the students’ science process skills before and after as well as the differences in the science process skills before and after applying guided inquiry learning model on the material reaction rate. The form of research used is pre-experimental design and the research design used is one-group pretest-posttest design. Subject in this study is the students of class XI IPA SMA Kristen Abdi Wacana. Data collection tools used is science process skill tests. After data processing, the pretest’s result shows 4.54% are skilled students and 90.9% of the students are in unskilled category, while posttest result shows 54,54% students are in skilled category and 9,09% are unskilled. Data analysis using Wilcoxon test (α = 5%) obtained by Asymp value. Sig. (2-tailed) by 0,000. This can be concluded that there are differences of students' science process skill before and after applying guided inquiry learning model.Keywords: Guided Inquiry Model, Science Process Skills, Rate of Reaction